Multimedia Learning: An Activity Based Computer to Develop Reading Comprehension - Sulistianingsih, Endang; Prihatin, Fajar; Mulyati, Sri (Lingual Journal of Language and Culture; Vol 6 No 2 (2018): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2018.v06.i02.p01, 2019)
Abstract               The aimed of the study was to find out the effectively of multimedia learning as an activity based computer to develop reading comprehension. The students’ comprehension development is crucial to help students to be success in following development of science and technology, since most of the scientific works are released in English. This research used experimental design with pre-test and posttest one design. There were 47 students as a participants. The pre-test was done to test the sample similarity and the initial level of student’s reading comprehension. The movies given during the intervention session. Then the evaluation and post-test were done to find out the student’s reading comprehension development. Hypothesis was tested using t-test. The result indicated that multimedia learning as an activity based computer was effective to develop student’s reading comprehension.    Keywords: Multimedia, Computer, Reading Comprehension, CALL, EFL learner